Platinum-based catalyst and preparation and application thereof
By using hydroxyapatite and iron oxide composite support to coat platinum nanoparticles, the metal support strong interaction (SMSI) technology is used to solve the problem of catalyst inactivation under high temperature conditions, and the preparation of platinum-based catalysts with high activity and high stability is achieved, which is suitable for CO oxidation reactions.
Patent Information
- Application Number
- CN202311058217.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to improve the anti-sintering performance of the supported metal catalyst while maintaining catalytic activity, resulting in the catalyst being inactivated under high temperature conditions, and the regeneration process is complex and costly.
A composite support composed of hydroxyapatite and iron oxide was used to prepare a platinum-based catalyst by co-precipitation method and electrostatic adsorption method. The metal support strong interaction (SMSI) was used to coat the platinum nanoparticles with the support, adjust the permeability of the coating layer, and maintain the high temperature stability and activity of the catalyst.
The high activity and high stability of the platinum-based catalyst are achieved, and can operate continuously for 200 hours in the CO oxidation reaction and the conversion rate is stable, which reduces production costs and increases the utilization rate of the catalyst.
Smart Images

Figure CN119500200A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of catalytic technology, and specifically relates to a preparation method and application of a supported high-activity and high-stability platinum-based catalytic material based on a strong interaction between metal carriers. In particular, for a composite carrier composed of hydroxyapatite and iron oxide, the active species is a platinum catalyst. After high-temperature calcination in an oxidizing atmosphere, a strong metal-carrier interaction occurs between the platinum and the carrier, and the platinum nanoparticles are coated by the carrier, which inhibits particle sintering and agglomeration. Due to the addition of iron oxide species, the permeability of the coating layer is adjusted, and a synergistic effect is generated between the two different types of carriers. The unique coating structure not only provides high-temperature stability of the catalyst, but also the presence of iron oxide can modulate the interaction between the metal and the carrier, maintaining the good activity of the catalyst. The method is simple and easy to implement, and provides a preparation method and application for preparing a highly active and highly stable supported platinum-based catalyst. Background Art
[0002] Supported metal catalysts occupy a major position in the industrial application of heterogeneous catalysts. In addition to mechanical strength, anti-dissolution and anti-decomposition properties, the interaction between the catalyst support and the metal has a significant impact on the performance of the catalyst. Supported metal nanoparticles are easily sintered or leached under harsh reaction conditions, resulting in catalyst deactivation. The regeneration of the catalyst requires separating the metal species from the support and re-loading them to obtain a new catalyst. This process is complicated and costly, especially for precious metal catalysts. Therefore, researchers have used various strategies to improve the anti-sintering properties of catalysts, and the preparation of highly active and highly stable supported catalysts is an important topic in the field of heterogeneous catalysis.
[0003] In recent years, researchers have developed a series of strategies to prepare sintering-resistant and efficient metal-based catalysts. These mainly include various means such as using strong metal-support interaction (SMSI), encapsulating active species particles in pore materials, and fixing them in zeolite crystals. These methods do improve the high-temperature sintering resistance or reaction stability of the catalyst to a certain extent, but at the same time, due to the presence of the covering layer, the number of active sites on the metal surface is reduced, that is, the cost of sintering resistance is to reduce the activity of the catalyst. Tauster et al. first proposed the concept of "strong metal-support interaction" in 1978. It is used to explain the phenomenon that the chemical adsorption capacity of Pt / TiO2 catalyst for H2 and CO is significantly reduced after high-temperature reduction treatment. A series of subsequent studies have confirmed that the SMSI phenomenon can not only be formed during high-temperature reduction, but also during high-temperature oxidation treatment, accompanied by the coating of the carrier on the surface of the metal particles. Compared with other anti-sintering strategies, SMSI not only has simple operation steps such as high-temperature oxidation-reduction treatment, but also can regulate catalyst performance through electron transfer between metal and carrier.
[0004] At present, there are few reports that can improve the sintering resistance of catalysts while maintaining the catalytic activity of catalysts. Therefore, the purpose of this patent is to regulate the strong interaction between metal carriers and develop a method to make supported catalysts have excellent stability and maintain good catalytic activity. This is of great significance to improving catalyst utilization and reducing production costs. Summary of the invention
[0005] The present invention provides a preparation method and application of a platinum-based catalyst with high activity and high stability based on strong interaction regulation of metal carriers. The preparation process of the method is simple, the loading amount of precious metal platinum is low (loading amount 0.5-10wt%), and the obtained catalyst exhibits good activity and excellent stability for CO oxidation reaction.
[0006] To achieve the above purpose, the present invention firstly prepares a mixed carrier of hydroxyapatite and iron oxide by a coprecipitation method, and then uniformly disperses platinum on the carrier by an electrostatic adsorption method.
[0007] The specific catalyst preparation process is as follows:
[0008] 1) Under Ar atmosphere, first dissolve soluble salts of divalent iron (concentration 5.0-30.0mmol / L) and trivalent iron (concentration 10.0-60.0mmol / L) in 50-80mL of deoxygenated water. 2+ and Fe 3+The molar ratio of 1:2 is 1:2, and ultrapure water is boiled at 140°C for 15-40 minutes to prepare deoxygenated water; then 40-80mL of ammonia water (mass concentration 25%) is added to the above solution to obtain a suspension containing a black precipitate of iron oxide, and the suspension is stirred at room temperature for 10-30 minutes;
[0009] Ammonia water is added to the calcium source solution and the phosphorus source solution to adjust the pH to 8-11, and then equal volumes of the calcium source solution and the phosphorus source solution (keeping the Ca / P atomic ratio of 5:3) are simultaneously added dropwise to the above-mentioned iron oxide solution under stirring; after the addition is completed, the suspension is reacted in a 60-90°C water bath for 1-6 hours, and then allowed to stand at room temperature and aged for 12 hours; the obtained solid product is centrifuged, washed with water to neutrality, freeze-dried, and calcined in an air atmosphere at 200-400°C for 3-6 hours, and the obtained yellow powder product is marked as xFe-HAP carrier (xFH, x represents the mass percentage of iron oxide in the carrier x = 1-30%); 2) Preparation of catalyst: Platinum is supported by electrostatic adsorption method, specifically, the concentration is 0.01-1mg Pt mL -1 (Preferably 0.1-0.5 mg Pt mL -1 ) of a precursor solution of a Pt species, add 1.0 g of the above carrier, stir continuously at room temperature for 6-12 hours, centrifuge and wash the product, and then dry it at 50-80° C. for 8-20 hours. Subsequently, it is further calcined in air at a calcination temperature of 400-800° C. (preferably 400-600° C., more preferably 500-600° C.) for 2-5 hours to obtain a platinum catalyst with high activity and stability.
[0010] The activity test method of the catalyst prepared by the present invention is as follows:
[0011] The CO catalytic oxidation reaction is carried out at atmospheric pressure in a micro fixed bed reactor. The raw gas contains CO and O2, He is used as the balance gas, O2 content is 1-10 vol%, CO content is 1-10 vol%, O2 raw gas space velocity is 20L gcat -1 h -1 Before the test, He gas was introduced into the catalyst bed for 30 minutes at room temperature. The reaction temperature was 20-600°C, and the catalyst bed temperature was controlled using a tubular furnace under thermocouple monitoring. The reaction products were analyzed online using an Agilent 6890 chromatograph equipped with a TCD detector. The CO conversion rate was calculated as follows:
[0012]
[0013] Catalyst activity evaluation selection T 50 and T 100 As an evaluation index for comparison, (Co inis the chromatographic peak area of CO in the raw gas, CO out is the chromatographic peak area of CO at the outlet after the reaction), and the corresponding conversion temperature when the CO conversion rate is 50% is T 50 , CO full conversion temperature is T 100 The lower the temperature required for conversion, the better the activity of the corresponding catalyst.
[0014] The catalyst preparation method and application of the present invention have the following effects:
[0015] The carrier used in the present invention is a carrier composited with hydroxyapatite and iron oxide. The active species platinum is loaded on the carrier by an electrostatic adsorption method. After high-temperature calcination in an oxidizing atmosphere, a strong metal-carrier interaction is generated between the platinum nanoparticles and the carrier. The method is simple to operate and widely used. The characterization results show that the platinum nanoparticles dispersed on the surface of the composite carrier are wrapped by the carrier, and the coating of the Pt particles by hydroxyapatite in an oxidizing atmosphere makes the catalyst have excellent stability. The catalyst prepared by the present invention can be used for CO catalytic oxidation. Under the reaction conditions, it is continuously operated for 200 hours, and the conversion rate of CO has no obvious downward trend. Moreover, the catalyst after calcination maintains the activity before calcination, realizing the preparation of a Pt-based catalyst with both stability and high activity, showing good development potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of the change of CO oxidation conversion rate with temperature for the catalysts prepared in Example 1 and Comparative Examples 1 and 2 (reaction gas composition: 1 vol% CO + 1 vol% O2 + 98 vol% He; gas flow rate: 33.3 ml.min -1 );
[0017] Figure 2 This is a TEM image of the catalyst of Example 1. In the catalyst, Pt is dispersed on the surface of the carrier in the form of nanoparticles, with a particle size range of 0.3-5 nm. There is a coating layer on the surface of the Pt particles with a thickness range of 0.5-2.0 nm ( Figure 2 a resolution of 10nm, Figure 2 b resolution is 5nm);
[0018] Figure 3 This is a long-term (200 h) stability evaluation of the catalyst of Example 1 for catalytic CO oxidation. DETAILED DESCRIPTION
[0019] In order to further explain the present invention in detail, the following examples are listed, but the scope of the claims of the present invention is not limited by these examples. At the same time, the examples only provide some conditions for achieving this purpose, but do not mean that these conditions must be met to achieve this purpose.
[0020] Examples 1-14
[0021] 1. Investigate the influence of carrier preparation conditions on catalyst performance
[0022] 1) The carrier was prepared by coprecipitation. Under Ar atmosphere, FeCl2·4H2O (concentration range 2.5-30.0mmol / L, specifically 13.9mmol / L) and ferric iron (concentration range 5.0-60.0mmol / L, specifically 27.7mmol / L) were dissolved in 60mL of deoxygenated water. 2+ and Fe 3+ The molar ratio of the above solution is 1:2; then 60mL of ammonia water (mass concentration 25%) is added to the above solution to obtain a suspension containing a black precipitate of iron oxide, and stirred at room temperature for 15 minutes; 80mL of a calcium source solution with a concentration of 0.2-0.8mol / L and 80mL of a phosphorus source solution with a Ca / P atomic ratio of 5:3 are added with ammonia water (mass concentration 25%) to adjust the pH to 10.3, and then the calcium source solution and the phosphorus source solution are simultaneously added dropwise to the above iron oxide solution under stirring; after the addition is completed, the suspension is reacted in a 60-90℃ water bath for 1-6h, and then allowed to stand at room temperature and aged for 12h; the obtained solid product is centrifuged, washed with water to neutrality, freeze-dried, and calcined at 400℃ in air atmosphere for 5 hours, and the obtained product is marked as 5Fe-HAP carrier (abbreviated as 5FH, 5 represents that the theoretical mass fraction of iron oxide in the carrier is 5wt%);
[0023] 2) Preparation of catalyst: Platinum was loaded by electrostatic adsorption method. Specifically, 150 mL of catalyst with a concentration of 0.33 mg Pt / mL K2PtCl4 solution, add 1.0g of the above support, stir continuously at room temperature for 12h, centrifuge and wash the product, then dry at 60°C for 12h. Then, calcine at 600°C in air for 3h to obtain a high-activity and high-stability noble metal platinum catalyst.
[0024] The catalytic oxidation of CO was used as a model reaction to investigate the performance of various catalysts synthesized under different carrier preparation conditions. The reaction was carried out in a micro fixed bed reactor under atmospheric pressure. The feed gas space velocity was 20 L·gcat -1 ·h -1 , the composition is 1vol%CO+1vol%O2+98vol%He. Before the test, He gas was introduced into the catalyst bed for 30 minutes at room temperature, and then the catalyst bed temperature was regulated using a tubular furnace under thermocouple monitoring. The reaction products were analyzed online using an Agilent 6890 chromatogram equipped with a TCD detector. The CO conversion rate was calculated as follows:
[0025]
[0026] Catalyst activity evaluation selection T 50 and T 100 As an evaluation index for comparison, (Co in is the chromatographic peak area of CO in the raw gas, CO out is the chromatographic peak area of CO at the outlet after the reaction), and the corresponding conversion temperature when the CO conversion rate is 50% is T 50 , CO full conversion temperature is T 100 The lower the temperature required for conversion, the better the activity of the corresponding catalyst.
[0027] Table 1 Effect of carrier preparation conditions on catalyst performance
[0028]
[0029] Note: In the example, the theoretical value of the mass ratio of FeOx (based on the generated product being Fe2O3) to HAP is 5:95; the theoretical loading amount of Pt in the catalyst is 5.0wt%, and deoxygenated water is prepared by boiling ultrapure water at 140°C for 20 minutes.
[0030] As shown in Table 1, different soluble salts of trivalent iron have different effects on the activity. The catalyst synthesized by FeCl3·6H2O has the best activity. CaCl2 has poor activity as a calcium source, which may be due to the small amount of Cl remaining in the product. - It will adsorb on the surface of Pt species, causing some Pt sites to be deactivated; the catalyst activity is better when the Ca source concentration is low; different P source types have little effect on catalyst performance; the catalyst activity is better when the synthesis temperature is higher and the reaction time is longer, which may be due to the more uniform dispersion of the composite carrier. The Pt particle size range of the catalysts in Examples 1-14 above is 0.3-4nm, and the coating layer thickness range is 0.5-2.0nm.
[0031] Examples 15-29
[0032] 2. Investigate the influence of various conditions on catalyst performance during electrostatic adsorption of platinum
[0033] 1) The carrier was prepared by coprecipitation. Under Ar atmosphere, FeCl2·4H2O (concentration of 11.7mmol / L) and FeCl3·6H2O (concentration of 23.5mmol / L) were dissolved in 60mL of deoxygenated water. 2+ and Fe 3+ The molar ratio of is 1:2; then 60 mL of ammonia water (mass concentration 25%) is added to the above solution to obtain a suspension containing a black precipitate of iron oxide, and stirred at room temperature for 15 minutes;
[0034] Ammonia water (mass concentration 25%) was added to 80 mL of 0.4 mol / L Ca(NO3)2·4H2O solution and 80 mL of 0.24 mol / L (NH4)2HPO4 solution to adjust the pH to 10.3, and then the calcium source solution and the phosphorus source solution were simultaneously added dropwise to the above iron oxide solution under stirring; after the addition was completed, the suspension was reacted in a 90°C water bath for 2 h, and then allowed to stand at room temperature and aged for 12 h; the obtained solid product was centrifuged, washed with water to neutrality, freeze-dried and calcined at 400°C in air atmosphere for 5 hours, and the obtained yellow powder product was marked as 5Fe-HAP carrier (5FH, 5 represents the mass fraction of iron oxide in the carrier is 5wt%);
[0035] 2) Preparation of catalyst: Platinum was loaded by electrostatic adsorption method. Specifically, 150 mL of catalyst with a concentration of 0.01-1 mg was prepared. Pt / mL of a precursor solution of Pt species, add 1.0g of the above-mentioned carrier, stir continuously at room temperature for 6-12h, centrifuge and wash the product, and then dry it at 60°C for 12 hours. Subsequently, it is further calcined in air at a calcination temperature of 400-800°C for 2-5 hours to obtain a platinum catalyst with high activity and stability.
[0036] The catalytic oxidation of CO was used as a model reaction to investigate the performance of various catalysts synthesized under different carrier preparation conditions. The reaction was carried out in a micro fixed bed reactor under atmospheric pressure. The feed gas space velocity was 20 L·gcat -1 ·h -1 , the composition is 1vol%CO+1vol%O2+98vol%He. Before the test, He gas was introduced into the catalyst bed for 30 minutes at room temperature, and then the catalyst bed temperature was regulated using a tubular furnace under thermocouple monitoring. The reaction products were analyzed online using an Agilent 6890 chromatogram equipped with a TCD detector. The CO conversion rate was calculated as follows:
[0037]
[0038] Catalyst activity evaluation selection T 50 and T 100 As an evaluation index for comparison, (Co in is the chromatographic peak area of CO in the raw gas, CO out is the chromatographic peak area of CO at the outlet after the reaction), and the corresponding conversion temperature when the CO conversion rate is 50% is T 50 , CO full conversion temperature is T 100 The lower the temperature required for conversion, the better the activity of the corresponding catalyst.
[0039] Table 2 Effect of various conditions on catalyst performance during electrostatic adsorption loading of platinum
[0040]
[0041]
[0042] Note: In the example, the theoretical value of the mass ratio of FeOx (based on the generated product being Fe2O3) to HAP is 5:95; the theoretical loading amount of Pt in the catalyst is 5.0wt%, and deoxygenated water is prepared by boiling ultrapure water at 140°C for 20 minutes.
[0043] It can be seen from Table 2 that among different Pt precursors, the catalyst using K2PtCl4 has the best activity, which may be because it is easier to adsorb on the carrier surface during the electrostatic adsorption process; when the Pt concentration is higher, the catalyst activity is better, but it should not be too high to affect the adsorption process; the longer the adsorption time, the better the activity, which may be because the time is short and Pt is less adsorbed on the carrier surface; calcination temperature that is too high or too low is not conducive to improving the activity of the catalyst; the particle size of the Pt particles in the catalysts of Examples 26, 28, and 29 is in the range of 0.5-5nm, and the coating layer thickness is in the range of 1.5-4nm. The particle size of the Pt particles in the catalysts of Examples 15-25 and 27 is in the range of 0.3-4nm, and the coating layer thickness is in the range of 0.5-2.0nm. The longer the calcination time, the worse the catalyst activity, which may be because the coating layer becomes thicker and covers part of the active sites.
[0044] Examples 30-35
[0045] 3. Investigate the effect of different mass fractions of iron oxide in the carrier on the catalyst performance
[0046] 1) The carrier was prepared by coprecipitation. Under Ar atmosphere, appropriate amounts of FeCl2·4H2O and FeCl3·6H2O were dissolved in 60 mL of deoxygenated water. 2+ and Fe 3+ The molar ratio of is 1:2; then 60 mL of ammonia water (mass concentration 25%) is added to the above solution to obtain a suspension containing a black precipitate of iron oxide, and stirred at room temperature for 15 minutes;
[0047] Ammonia water (mass fraction 25%) was added to 80 mL of Ca(NO3)2·4H2O aqueous solution and 80 mL of (NH4)2HPO4 aqueous solution respectively to adjust the pH to 10.3, and keep the Ca / P atomic ratio at 5:3, and then the calcium source solution and the phosphorus source solution were simultaneously added dropwise to the above iron oxide solution under stirring; after the addition was completed, the suspension was reacted in a 90°C water bath for 2 hours, and then allowed to stand at room temperature and aged for 12 hours; the obtained solid product was centrifuged, washed with water to neutrality, freeze-dried and calcined at 400°C in air atmosphere for 5 hours, and the obtained yellow powder product was marked as xFe-HAP carrier (xFH, x represents the mass fraction of iron oxide in the carrier x = 1-30wt%);
[0048] 2) Preparation of catalyst: Platinum was loaded by electrostatic adsorption method, and 150 mL was prepared with a concentration of 0.33 mg Pt / mL K2PtCl4 solution, add 1.0g of the above carrier, stir continuously at room temperature for 12h, centrifuge and wash the product, and then dry it at 60℃ for 12h. Then further calcinate it at 600℃ in air for 3h to obtain a high-activity and high-stability noble metal platinum catalyst. Marked as Pt / xFH-600 (x represents the mass fraction of iron oxide in the carrier x=1-30wt%);
[0049] The catalytic oxidation of CO was used as a model reaction to investigate the effect of different mass fractions of iron oxide in the carrier on the performance of each catalyst. The reaction was carried out in a micro fixed bed reactor under atmospheric pressure. The feed gas space velocity was 20L gcat -1 h -1 , the composition is 1vol%CO+1vol%O2+98vol%He. Before the test, He gas was introduced into the catalyst bed for 30 minutes at room temperature, and then the catalyst bed temperature was controlled using a tubular furnace under thermocouple monitoring. The reaction products were analyzed online using an Agilent6890 chromatogram equipped with a TCD detector. The CO conversion rate was calculated as follows:
[0050]
[0051] Catalyst activity evaluation selection T 50 and T 100 As an evaluation index for comparison, the conversion temperature corresponding to the CO conversion rate of 50% is T 50 , CO full conversion temperature is T 100 The lower the temperature required for conversion, the better the activity of the corresponding catalyst.
[0052] Table 3 Effect of different mass fractions of iron oxide in the carrier on catalyst performance
[0053]
[0054] NOTE: The theoretical loading of Pt in the catalyst is 5.0 wt%. Deoxygenated water was prepared by boiling ultrapure water at 140 °C for 20 min.
[0055] It can be seen from Table 3 that the mass fraction of iron oxide in the carrier has a significant effect on the activity of the catalyst. 50 The lower the value, the better the catalyst activity. 50By comparison, it can be seen that the higher the iron oxide content in the carrier, the better the catalyst activity. The catalytic activity of the iron oxide content higher than 10% decreases with the increase of the iron oxide mass fraction. However, for samples with an iron oxide content lower than 10%, the catalytic activity decreases with the decrease of the iron oxide content. When the mass fraction of iron oxide in the carrier is 5%, the Pt / 5FH-600 catalyst has the best activity. The Pt particle size range of the catalysts in the above Examples 30-35 is 1-4nm, and the surface coating thickness ranges from 0.5-2.0nm.
[0056] Embodiment 36
[0057] Catalyst performance evaluation
[0058] 100 mg of the (Pt / 5FH-600) catalyst prepared in Example 1 was uniformly mixed with 130 mg of SiO2 powder and then loaded into a quartz tube reactor. The catalyst was first purged in a He atmosphere at room temperature for 30 min and then used for the evaluation of CO oxidation performance after the purging was completed. The evaluation conditions were the same as in Example 1. Figure 1 The catalyst in Example 1 can achieve complete conversion of CO at 140°C and has good catalytic activity.
[0059] Embodiment 37
[0060] Investigation of Pt particle size and surface coating in catalysts
[0061] Take 2 mg of the (Pt / 5FH-600) catalyst prepared in Example 1, disperse it in 2 mL of anhydrous ethanol solution, ultrasonicate it for 10 min to make it evenly dispersed, drip it onto a copper grid drop by drop, dry it with an infrared lamp, and perform TEM test. Figure 2 As shown in a, electron microscopy characterization confirmed that the Pt in the catalyst was dispersed on the surface of the carrier in the form of nanoparticles with a particle size range of 0.3-4nm. Figure 2 As shown in b, a coating layer is formed on the surface of the Pt nanoparticles, and the thickness of the coating layer is between 0.5-2.0nm.
[0062] Embodiment 38
[0063] Evaluation of catalyst stability
[0064] 3.5 mg of the Pt / 5FH-600 catalyst prepared in Example 1 was mixed with 230 mg of SiO2 powder and loaded into a quartz tube reactor. The catalyst was first purged in a He atmosphere at room temperature for 30 min. After the purging, it was used to evaluate the CO oxidation performance under the same evaluation conditions as in Example 1. Figure 3As shown, the test results show that when catalyzing the CO oxidation reaction at 300°C, the conversion rate did not decrease significantly during the 200-hour test, indicating that the preparation of Pt-based catalysts with both high activity and stability was achieved by regulating the strong interaction between metal supports through the design of the support.
[0065] Comparative Example 1
[0066] Pt / HAP
[0067] Weigh 7.53g Ca(NO3)2·4H2O and 2.53g (NH4)2HPO4 and dissolve them in 80mL water respectively, keep the calcium-phosphorus atomic ratio (Ca / P) at 1.67, adjust the pH of the two solutions to 10.3 with ammonia water (mass fraction 25%), and then drop the two solutions into 15mL ammonia water (25%) under vigorous stirring. After the addition is completed, the white suspension is reacted in a 90℃ water bath for 2h, then allowed to stand at room temperature and aged for 12h. The obtained product is centrifuged and washed to neutrality, freeze-dried and calcined at 400℃ in air atmosphere for 5h, and the obtained white powder product is marked as HAP carrier.
[0068] The concentration is 0.33 mg in 150 mL Pt 1.0 g of the HAP support prepared above was added to a 1.5 / mL K2PtCl4 solution, and the mixture was stirred vigorously at room temperature for 12 hours. The catalyst was centrifuged, washed with water, and then dried at 60°C for 12 hours. It was then calcined at 600°C in air for 3 hours and labeled as Pt / HAP-600.
[0069] The catalyst performance evaluation method is the same as in Example 1.
[0070] Comparative Example 2
[0071] Pt / FeOx
[0072] Under Ar gas protection, 4.0 g of FeCl3·6H2O and 1.47 g of FeCl2·4H2O were added to 60 mL of deoxygenated water (prepared by boiling ultrapure water at 140°C for 20 minutes) and dissolved. 2+ and Fe 3+ The molar ratio of 1:2 was 1:2, and after being mixed evenly, 60 mL of ammonia water (mass concentration 25%) was added thereto to obtain a suspension containing a black precipitate of iron oxide; after stirring at room temperature for 15 minutes, the above solution was reacted in a 90°C oil bath for 2 hours, and then allowed to stand at room temperature for aging for 12 hours. The obtained product was centrifuged, washed with water until neutral, freeze-dried, and calcined at 400°C in air atmosphere for 5 hours (heating rate was 5°C·min -1 ), and the obtained black powder product is marked as FeOx.
[0073] The concentration is 0.33 mg in 150 mLPt 1.0 g of the FeOx carrier prepared above was added to a 100 mL K2PtCl4 solution, and the mixture was stirred vigorously at room temperature for 12 hours. The catalyst was centrifuged, washed with water, and then dried at 60°C for 12 hours. It was then calcined at 600°C in air for 3 hours and labeled as Pt / FeOx-600.
[0074] The catalyst performance evaluation method is the same as in Example 1.
[0075] Comparative Example 3
[0076] Pt / FeOx-HAP
[0077] The separately prepared FeOx and HAP were directly physically mixed, wherein the mass fraction of FeOx was 5 wt %, and the mixture was directly used as a carrier and was marked as FeOx-HAP.
[0078] The concentration is 0.33 mg in 150 mL Pt 1.0 g of the FeOx support prepared above was added to a 100 mL K2PtCl4 solution, and the mixture was stirred vigorously at room temperature for 12 hours. The catalyst was centrifuged, washed with water, and then dried at 60°C for 12 hours. It was then calcined at 600°C in air for 3 hours and labeled as Pt / FeOx-HAP-600.
[0079] The catalyst performance evaluation method is the same as in Example 1.
[0080] Table 4 Comparison of catalyst performance between Example 1 and Comparative Examples 1-3
[0081]
[0082] Note: The theoretical loading of Pt in the catalyst is 5.0 wt%.
[0083] Through Table 4 and Figure 1 The comparison of Example 1 and Comparative Examples 1-2 in the conversion rate curve can draw the following conclusions:
[0084] The type of catalyst support has a significant effect on catalytic performance. Figure 1 The performance diagram of CO conversion rate and experimental temperature of each catalyst can intuitively compare its catalytic activity. Compared with the catalyst with a single carrier, Pt / 5FH-600 has significantly better activity. The synergistic effect between the two carriers and the metal particles avoids the phenomenon that the catalyst activity is significantly deteriorated during the 600°C high temperature treatment process. The preparation method designed by the present invention can achieve high activity and high stability of the catalyst, but directly mixing FeOx and HAP as a carrier fails to maintain the original activity after calcination. It can be seen that the unique preparation method is crucial for regulating the strong interaction between the metal and the carrier.
Claims
1. A platinum-based catalyst, characterized in that: The catalyst carrier is a mixture of hydroxyapatite and iron oxide. The active component platinum is loaded on the carrier surface in the form of nanoparticles (0.3-5nm). After calcination, the surface of the platinum nanoparticles is coated by the carrier hydroxyapatite, and the coating layer thickness is 0.5-5nm (preferably 0.5-2nm).
2. The catalyst according to claim 1, characterized in that: The content of active component platinum in the catalyst ranges from 0.5-10wt% (preferably 0.5-5wt%, more preferably 0.5-3%), and the mass fraction of iron oxide in the carrier ranges from 1-30wt% (preferably 1-10wt%, more preferably 3-10%) to the total mass of the carrier.
3. The method for preparing the catalyst according to any one of claims 1 or 2, comprising the following steps: 1) Preparation of carrier: The carrier is prepared by coprecipitation method: Under Ar gas protection, firstly, dissolve soluble salts of divalent iron (preferably 0.03-1g, more preferably 0.1-0.5g) and trivalent iron (preferably 0.05-5g, more preferably 0.2-2g) in 50-80mL of deoxygenated water. 2+ and Fe 3+ The molar ratio is 1:2; then 40-80mL of ammonia water is added to the above solution to obtain a suspension containing a black precipitate of iron oxide, and stirred at room temperature for 10-30 minutes; Ammonia water is added to the calcium source solution and the phosphorus source solution to adjust the pH to 8-11, and then equal volumes of the calcium source solution and the phosphorus source solution (keeping the Ca / P atomic ratio at 5:3) are simultaneously added dropwise to the above iron oxide solution under stirring; After the addition is completed, the suspension is reacted in a 60-90°C water bath for 1-6 hours, then allowed to stand at room temperature and aged for 12 hours; the obtained solid product is centrifuged, washed with water until neutral, freeze-dried, and then calcined in an air atmosphere at 200-400°C for 3-6 hours. The obtained yellow powder product is marked as xFe-HAP carrier (xFH, x represents the mass percentage of iron oxide in the carrier x = 1-30%); 2) Preparation of catalyst: Preparation of supported platinum catalyst by electrostatic adsorption method; specifically, The preparation concentration is 0.01-1mg Pt / mL (preferably 0.1-0.5mg Pt / mL) of a precursor solution of a Pt species, add the above-mentioned carrier thereto, stir continuously at room temperature for 6-12 hours, centrifuge and wash the product, and then dry it at 50-80°C for 8-20 hours; subsequently, further calcinate it in air at a calcination temperature of 400-800°C (preferably 400-600°C, more preferably 500-600°C) and a calcination time of 2-5 hours to obtain a platinum catalyst.
4. The preparation method according to claim 3, characterized in that: The deoxygenated water is prepared by boiling ultrapure water at 140° C. for 15-40 minutes, the mass concentration of the ammonia water is 25%, the concentration of the calcium source is 0.2-0.8 mol / L, and the concentration of the phosphorus source is 0.12-0.48 mol / L.
5. The preparation method according to claim 3, characterized in that: The calcium source can be one or more of soluble calcium salts such as calcium chloride and calcium nitrate, the phosphorus source can be one or more of soluble phosphates such as diammonium hydrogen phosphate and ammonium dihydrogen phosphate, and the soluble iron salt can be one or more of ferric chloride, ferric nitrate, ferric sulfate and ferrous chloride.
6. The method for preparing the catalyst according to claim 3, characterized in that: The precursor of the Pt species is one or more of chloroplatinic acid, platinum nitrate, tetraammine platinum nitrate, platinum acetylacetonate, and potassium chloroplatinite, preferably potassium chloroplatinite.
7. Use of the catalyst according to claim 1 or 2 in catalytic oxidation reactions.
8. The use according to claim 7, characterized in that: Application in oxidation reactions such as CO catalytic oxidation and elimination of CO in automobile exhaust.
9. The use according to claim 7 or 8, characterized in that: The catalyst is used in catalytic CO oxidation reaction. The CO content in the raw gas is 1-5 vol%, the O2 content is 1-10 vol%, and the rest is inert gas He as balance gas; the volume space velocity is 20-80 L g cat –1 h -1 , the reaction pressure is normal pressure, and the reaction temperature is 20-800°C (preferably 20-600°C, more preferably 20-400°C).